Pipe Failure Probabilities of Water Distribution Systems - Syarifah Hidayah Syed Harun; Ismail Bin Mohd (Program Studi Statistika Unisba, 2011)
In this paper, we will describe two methods so-called Poisson method and Generic Expectation Function (GEF)method for using to find pipe failure probabilities of water distribution systems which implicitly designed byengineers. In order to develop GEF method using means and coefficients of variation of input randomvariables through employing probability distribution such as normal distribution, is adopted. In this paper, 9water distribution systems which are located in Terengganu, Malaysia and 1 hypothetical water distributionsystem, have been used for illustrating these mentioned both methods from which the comparison can bediscussed. Besides that, hydraulic simulation software, EPANET has been applied to get the input variables foreach project. Failure probability of each pipe is focused on failure probability of pipe to fulfil the demanddenoted by PA and also pipe replacement probability denoted by PB.